Isotope fractionation of micropollutants during large-volume extraction: heads-up from a critical method evaluation for atrazine, desethylatrazine and 2, 6-dichlorobenzamide at low ng/L concentrations in groundwater. Issue 1 (2nd January 2021) - Melsbach, Aileen; Pittois, Denis; Bayerle, Michael; Daubmeier, Martina; Meyer, Armin H.; Hölzer, Kathrin; Gallé, Tom; Elsner, Martin
ABSTRACT: Micropollutants are frequently detected in groundwater. Thus, the question arises whether they are eliminated by natural attenuation so that pesticide degradation would be observed with increasing residence time in groundwater. Conventional analytical approaches rely on parent compound/metabolite ratios. These are difficult to interpret if metabolites are sorbed or further transformed. Compound-specific stable isotope analysis (CSIA) presents an alternative for identifying degradation based on the analysis of natural isotope abundances in pesticides and their changes during degradation. However, CSIA by gas chromatography–isotope ratio mass spectrometry is challenged by the low concentrations (ng/L) of micropollutants in groundwater. Consequently, large amounts of water need to be sampled requiring enrichment and clean-up steps from interfering matrix effects that must not introduce artefacts in measured isotope values. The aim of this study was to evaluate the accuracy of isotope ratio measurements of the frequently detected micropollutants atrazine, desethylatrazine and 2, 6-dichlorobenzamide after enrichment from large water volumes (up to 100 L) by solid-phase extraction with consecutive clean-up by HPLC. Associated artefacts of isotope discrimination were found to depend on numerous factors including organic matter content and extraction volume. This emphasizes the necessity to perform a careful method evaluation of sample preparation and sample pre-treatment prior reliable CSIA.